The Pengaruh Kualitas Produk, Harga, dan Content Marketing terhadap Minat Beli Konsumen - Qastalano, Rezha Isyraqi; Nugroho, Rizky Adhitya (Politeknik Sawunggalih Aji, 2024)
This study aims to examine the influence of product quality, price, and content marketing on the buying interest of consumers who buy Mixue products at Mixue outlets in the Mojokerto area. The population in this study is consumers who purchase Mixue products at Mixue outlets in the Mojokerto area. The sample used was 100 respondents using non-probability sampling techniques and types of purposive sampling methods. This data analysis uses SPSS 22 with a multiple linear regression method by conducting a classical assumption test first. The results of this study showed that product quality had a significant effect on buying interest, price did not have a significant effect on interest and content marketing had a significant effect on buying interest. The adjusted R Square value obtained was 0.462, so the influence of independent variables on dependent variables simultaneously was 46.2%..